Tracing back multidrug-resistant bacteria in fresh herb production: from chive to source through the irrigation water chain. Issue 11 (7th August 2018) - Gekenidis, Maria-Theresia; Schöner, Ulrich; von Ah, Ueli; Schmelcher, Mathias; Walsh, Fiona; Drissner, David
Abstract: Environmental antibiotic-resistant bacteria (ARB) can be transferred to humans through foods. Fresh produce in particular is an ideal vector due to frequent raw consumption. A major contamination source of fresh produce is irrigation water. We hypothesized that water quality significantly affects loads of ARB and their diversity on fresh produce despite various other contamination sources present under agricultural practice conditions. Chive irrigated from an open-top reservoir or sterile-filtered water (control) was examined. Heterotrophic plate counts (HPC) and ARB were determined for water and chive with emphasis on Escherichia coli and Enterococcus spp. High HPC of freshly planted chive decreased over time and were significantly lower on control- vs. reservoir-irrigated chive at harvest (1.3 log (CFU/g) lower). Ciprofloxacin- and ceftazidime-resistant bacteria were significantly lower on control-irrigated chive at harvest and end of shelf life (up to 1.8 log (CFU/g) lower). Escherichia coli and Enterococcus spp. repeatedly isolated from water and chive proved resistant to up to six or four antibiotic classes (80% or 49% multidrug-resistant, respectively). Microbial source tracking identified E. coli -ST1056 along the irrigation chain and on chive. Whole-genome sequencing revealed that E. coli -ST1056 from both environments were clonal and carried the same transmissible multidrug-resistance plasmid, proving water as source of chive contamination. These findings emphasize the urgent need for guidelines concerning ARB in irrigation water and development of affordable water disinfection technologies to diminish ARB on irrigated produce. Abstract : Irrigation water quality impacts on antibiotic-resistant bacteria of chive representing raw consumed fresh produce grown under agricultural practice conditions.